Victim-to-Victim Intergenerational Cycles of Child Maltreatment: A Systematic Scoping Review of Theoretical Frameworks - Marshall, Carley; Langevin, Rachel; Cabecinha-Alati, Sarah (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objectives: Child maltreatment is a serious problem worldwide associated with numerous developmental and psychological problems that can impede children’s short and long-term functioning. The negative effects of maltreatment may put children on a trajectory where they are likely to experience later abuse and even abuse their own children. While studies have focused primarily on the intergenerational transmission of maltreatment (victim-to-perpetrator cycles), there are studies, albeit fewer, documenting cycles of intergenerational continuity of maltreatment (victim-to-victim cycles; e.g., child sexual abuse). Clear theoretical frameworks are lacking from studies on intergenerational maltreatment. This review aimed to systematically identify theories, theoretical or conceptual frameworks that have been used to explain the victim-to-victim cycles of maltreatment. Methods: Searches were executed in PsychINFO, Medline, and Scopus. Fifteen papers were included in this review. Results: The most common theories used to explain the intergenerational continuity of maltreatment victimization were attachment theory and traumatic stress models. Other identified theories include those from social, developmental, and biological domains. Notably, there were only five papers on the intergenerational continuity of child sexual abuse, highlighting a lack of focus on the theoretical explanations of this issue. Based on the findings, a unified model of victim-to-victim cycles of maltreatment is proposed to guide future studies. Implications: Future research in this area could include testing and comparing theoretical explanations and advancing the current state of the literature by using qualitative and mixed methods.